Policy learning and change during crisis: COVID‐19 policy responses across six states. Issue 1 (9th October 2022) - Crow, Deserai A.; DeLeo, Rob A.; Albright, Elizabeth A.; Taylor, Kristin; Birkland, Tom; Zhang, Manli; Koebele, Elizabeth; Jeschke, Nathan; Shanahan, Elizabeth A.; Cage, Caleb
Abstract: Whereas policy change is often characterized as a gradual and incremental process, effective crisis response necessitates that organizations adapt to evolving problems in near real time. Nowhere is this dynamic more evident than in the case of COVID‐19, which forced subnational governments to constantly adjust and recalibrate public health and disease mitigation measures in the face of changing patterns of viral transmission and the emergence of new information. This study assesses (a) the extent to which subnational policies changed over the course of the pandemic; (b) whether these changes are emblematic of policy learning; and (c) the drivers of these changes, namely changing political and public health conditions. Using a novel dataset analyzing each policy's content, including its timing of enactment, substantive focus, stringency, and similar variables, results indicate the pandemic response varied significantly across states. The states examined were responsive to both changing public health and political conditions. This study identifies patterns of preemptive policy learning, which denotes learning in anticipation of an emerging hazard. In doing so, the study provides important insights into the dynamics of policy learning and change during disaster. Resumen: Mientras que el cambio de política a menudo se caracteriza como un proceso gradual e incremental, la respuesta efectiva a la crisis requiere que las organizaciones se adapten a los problemas en evolución casi en tiempo real. En ninguna parte esta dinámica es más evidente que en el caso de COVID‐19, que obligó a los gobiernos subnacionales a ajustar y recalibrar constantemente las medidas de salud pública y mitigación de enfermedades ante los patrones cambiantes de transmisión viral y la aparición de nueva información. Este estudio evalúa (a) la medida en que las políticas subnacionales cambiaron en el transcurso de la pandemia; (b) si estos cambios son emblemáticos del aprendizaje de políticas; y (c) los impulsores de estos cambios, a saber, las cambiantes condiciones políticas y de salud pública. Usando un nuevo conjunto de datos que analiza el contenido de cada política, incluido el momento de la promulgación, el enfoque sustantivo, el rigor y variables similares, los resultados indican que la respuesta a la pandemia varió significativamente entre los estados. Los estados examinados respondieron a cambios tanto en la salud pública como en las condiciones políticas. Este estudio identifica patrones de aprendizaje de políticas preventivas, lo que denota aprendizaje en previsión de un peligro emergente. Al hacerlo, el estudio proporciona información importante sobre la dinámica del aprendizaje y el cambio de políticas durante un desastre. 摘要: 虽然政策变革通常被描述为一个逐步和渐进的过程，但有效的危机响应需要组织近乎实时地适应不断变化的问题。这种动态在新冠疫情(COVID‐19)案例中表现得最为明显，面对病毒传播模式的变化和新信息的出现，地方政府被迫不断调整和重新修正公共卫生与疾病缓解措施。本研究评估了(a)地方政策在大流行期间的变化程度；(b)这些变化是否标志着政策学习；(c)这些变化的驱动因素，即不断变化的政治和公共卫生状况。使用一项新颖的数据集分析每项政策的内容，包括其制定时间、实质性重点、严格程度和类似变量，结果表明，各州对大流行的响应存在显著差异。各州对不断变化的公共卫生条件和政治条件都作出了响应。本研究识别了"预先的政策学习"模式，这表示在预期新危险时就进行政策学习。为此，本研究为灾害期间政策学习和政策变革的动态提供了重要见解。